Full utilization of nutrients in rice straw by integrating mushroom cultivation, biogas production, and fertilizer use - Huang, Wenbo; Wachemo, Akiber Chufo; Yuan, Hairong; Li, Xiujin (International Journal of Agricultural and Biological Engineering, 2019)
This study proposed an integrated process of Pleurotus ostreatus cultivation, anaerobic digestion of spent mushroom substrate (SMS), and fertilizer value evaluation of digestate for achieving multiple products and full utilization of nutrients in rice straw. The results showed that the cultivated mushroom yield from rice straw was 401 g/kg TS. Biomethane yield obtained from anaerobic digestion of SMS was 133.0 mL/g VS. The fertilizer value of the SMS based digestate reached the national standard of fertilizers from organic sources in China. Substance conversion of rice straw during the integrated process revealed that the process could achieve the full utilization of nutrients in the substrate. Energy assessment indicated that the process had the viability to be applied. Therefore, this study provided a feasible strategy to set up a complete recycling agricultural ecosystem. Keywords: rice straw, Pleurotus ostreatus, anaerobic digestion, fertilizer value, full utilization DOI: 10.25165/j.ijabe.20191204.4658 Citation: Huang W B, Wachemo A C, Yuan H R, Li X J. Full utilization of nutrients in rice straw by integrating mushroom cultivation, biogas production, and fertilizer use. Int J Agric & Biol Eng, 2019; 12(4): 174–183.